EVALUASI KINERJA SIMPANG BERSINYAL SEBELUM DAN SESUDAH PEMASANGAN INTELLIGENT TRAFFIC CONTROL SYSTEM (ITCS) (STUDI KASUS: SIMPANG BERSINYAL DASAN CERMEN KOTA MATARAM) - HASYIM, HASYIM; ROHANI, ROHANI; MASITA, MAYA (Universitas Mahasaraswati K. Mataram, 2024)
Intersections are an integral part of all road systems because they are places where traffic from two or more roads meets and changes direction. In Indonesia, the performance of intersections is controlled by traffic lights but still needs to be developed in order to meet the needs of drivers, where an efficient system is needed to control traffic flow. An Intelligent Traffic Control System (ITCS) is employed to enhance intersection efficiency and performance optimization. The ITCS system is expected to help reduce congestion because most of the traffic light intersections in Mataram City have ITCS devices installed.This research aims to asses the performance of the Dasan Cermen signalized intersection in Mataram City under conditions before and after the implementation of the Intelligent Traffic Control System (ITCS). The method used to analyze intersection performance is the Manual of Indonesian Road Capacity (MKJI) 1997.The research findings indicate that peak hours occur on Wednesday, 06.30 - 07.30 WITA with a traffic volume of 2320 pcu/hour. The performance of the intersection before the ITCS installation showed an average degree of saturation (DS) of 1.273, an average delay (D) of the intersection of 732.222 seconds/pcu and an average queue length (QL) of 399.004 m. The performance of the intersection after installing ITCS showed an average degree of saturation (DS) of 1.271, an average delay (D) at the intersection of 646,771 seconds/pcu and an average queue length (QL) of 381,919 m. After installing ITCS, there was an increase in intersection performance based on the degree of saturation (DS) of 0.2%, delay (D) of 10.6% and queue length (QL) of 4.3%.